Cultivo in vitro de Anaplasma marginale - Blandino, T.=700 1 Sanchez, A.; Alonso, M.
(Es, En)
Ilus., 6 ref.
Keywords: GANADO BOVINO; REPRODUCCION; BACTERIA; ANAPLASMA MARGINALE; CULTIVO IN VITRO; CUBA